PERAN KONSELING KELOMPOK DENGAN MENGGUNAKAN FILOSOFI TERAS DALAM MENGATASI PERILAKU BULLYING DI PANTI ASUHAN KELUARGA YATIM MUHAMMADIYAH (PAKYM) SURAKARTA TAHUN 2022 - Sari, Devita Nur Putri Arum (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2022)
Abstract: This study aimed to find out the role of Group Counseling with Filosofi Teras in solving Bullying behavior in Panti Asuhan Keluarga Yatim Muhammadiyah (PAKYM) Surakarta in 2022. To this end, A 4-cycle guidance and counseling action research was applied. Each cycle consisted of four stages: planning, action, observation, and reflection. The data source in this study were the bullies, orphan keeper, and the caregiver. Interviews, observation, and documentation were performed to collect the data. Techniques and sources of data in this study were triangulated to ensure the validity. The collected data were analyzed using the interactive data analysis technique. In this study, 6 participants were indicated to commit bullying behavior due to their poor regulation of emotion. Following interventions performed in each cycle, this study found that during the pre-cycle percentage of solved bullying behavior was 56.66%, Cycle I was 59,18%, Cycle II was 69.16%, Cycle III was 78.34%, and Cycle IV was 86.66%, respectively. Based on the study result, the group counseling with Filosofi Teras is applicable in overcoming bullying behavior in Panti Asuhan Keluarga Yatim Muhammadiyah (PAKYM) Surakarta in 2022. Keywords: Group Counseling, Filosofi Teras, Bullying Behavior.